Political Participation by the Deprived: A Comparative Analysis in Political Behavior by Unemployed Young Adults - Bassoli, Matteo; Lahusen, Christian (PARTECIPAZIONE E CONFLITTO, 2015)
For the SPECIAL SECTION EDITORIAL abstract is not required